Finite Mathematics and Calculus with Applications / Third Edition - Lial Margaret L.; Miller Charles D (Scott, Foresman And Company, 1989)
Index of Applications, Review of Algebra, Functions and Graphs, Systems of Linear Equations and Matrices, Linear Programming: The Graphical Method, Linear Programming: The Simplex Method, Sets and Counting, Probability, Statistics and Probability Distributions, Markov Chains and Decision Theory, Mathematics of Finance, The Derivative, Applications of the Derivative, Exponential and Logarithmic Functions, Integration, Further Techniques and Applications of Integration, Functions of Several Variables, Probability and Calculus, Tables, Answers to Selected Exercises, Index.